New Lithuanian compound proper names from the Old Lithuanian Metrica - Sinkevičiūtė, Daiva (Baltistica, 2018)
The article presents 48 new reconstructed and hitherto unknown Lithuanian compound proper names from the Lithuanian Metrica, made from stems already known from other names. Most of them occur in names of men recorded at the end of the 15th century and in the first half of the 16th century. Some of the names are made of two common Baltic stems, whereas others are made of a Lithuanian stem and a common Baltic stem, mostly as a second member. This shows that the second stem of compound proper names was more stable than the first stem. These names confirm that old anthroponyms of considerable interest for Lithuanian and Baltic onomastics can still be found in the sources.